Application of Cone Beam Computed Tomography to Conventional Radiotherapy: Limited Angle of Projections for Lymph Nodes Located above or below the Collarbone - Wataru Kawakami; Akihiro Takemura; Kunihiko Yokoyama; Kenichi Nakajima; Tetsu Nakaichi; Shoichi Yokoyama; Kichiro Koshida (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2015)
Various techniques are used in image-guided radiotherapy (IGRT). Cone  beam  computed tomography (CBCT) is widely used in IGRT on linear accelerators.The increased accuracy of IGRT enables reducing planning target volume margins and doses to normal tissues. However, for radiation therapies requiring  fractionated irradiation,increased  exposure dose attributed to CBCT becomes problematic. We  investigated the smallest projection angle required to provide target accuracy for CBCT of lymph nodes located above or below the collarbone in breast cancer patients.Phantom and clinical experiments were conducted on the basis of shifts obtained through gray value-based auto-image registration performed using 360° CBCT. Corrected images obtained from decreasing projection angles in 10° increments were compared with a single 360° image.In  the  phantom  and  clinical  experiments,the  smallest  projection  angle  used  as  the  tolerance level were 80° and 100°, which yielded the same accuracy as the 360° case. When irradiating lymph nodes above or below the collarbone with CBCT, a 100° projection angle was necessary for auto-image registration, whereas a projection angle of 195.8° (180° + fan) was required to produce artifact-free images.This  represents  95.8°  reductions  in  the  projection angle,resulting in a 48.9% reduction in exposure.